Islamic home finance products vis-a-vis failed residential projects in Malaysia: reality, issues and prospects - Md Dahlan, Nuarrual Hilal (2019)
The Malaysian government has established Islamic banking industry since in the 1980s. As a result, the Islamic banking industry in Malaysia has introduced various Islamic banking and finance products. However, hitherto the industry has also plagued the Islamic banking and finance products with multiple issues. One of the problems revolves around the issues of failed residential projects. Hence, this paper aims to study these issues, particularly, the terms in the prevailing Islamic Home Finance products (‘IHF’) in Malaysia vizBay’ Bithaman alAjil (‘BBA’), Musharakah al-Mutanaqisah (‘MM’), Commodity Murabahah (‘CM’) and IjarahMausufah Fi Zimmah (‘IMFZ’). Further, this paper will propose suggestions to improve the IHF products in dealing with the problems of failed residential projects. The author used shariah (Islamic Law), legal doctrinal and qualitative social and textual analysis research methodologies to study the subject matter and the issues. This paper finds that the applicable terms in the said products are inadequate and unfair. Thus, this has warranted the authority to replace the inequitable terms with conditions that can provide better protection to the aggrieved purchasers in failed residential projects, comply with the shariah and dispense justice to the contracting party purchaser customers. The author submits that the result of this paper will improve the theory and practice of Islamic home finance industry in Malaysia.